S54 Neural Respiratory Drive Measured Using Parasternal Intercostal Muscle Electromyography In Patients With Interstitial Lung Disease. (10th November 2014) - Kaaba, A; Jolley, C; MacBean, v; Reilly, C; Birring, S; Moxham, J; Rafferty, G
Abstract : Introduction: Forced vital capacity (FVC) and gas transfer (TLCO) are often used to assess disease severity and monitor progression in patients with interstitial lung disease (ILD). Difficulty in performing the required manoeuvres, particularly in severe disease, and inherent measurement variability makes detection of clinically important changes difficult using these parameters. There is, therefore, a need for new biomarkers in this patient group. Neural respiratory drive (NRD) reflects the load on the respiratory system and the capacity of the respiratory muscles. Parasternal intercostal muscle electromyography (EMGpara) provides a non-invasive measure of NRD which relates to disease severity and breathlessness in obstructive lung diseases. Measurements of EMGpara in ILD could potentially quantify overall disease severity. Aim: The aim of the study was to investigate the relationships between EMGpara, lung function, breathlessness, functional status and quality of life (QoL) in ILD. Method: EMGpara was measured in 45 patients with a range of fibrotic lung diseases using surface electrodes placed in the second intercostal spaces bilaterally. Mean peak root mean square EMGpara per breath was calculated and expressed as a percentage of maximum EMGpara (EMGpara%max). The neural respiratory drive index (NRDI) was derived by multiplying EMGpara%max by the respiratory rate. Spirometry and lung gas transfer were performed and the composite physiologic index (CPI) calculated. Six minute walk test (6MWT) and 4 metre gait speed (4MGS) were used to determine functional status. Health-related quality of life was assessed with the King's Brief Interstitial Lung Disease (K-BILD) and the St George's Respiratory Questionnaires (SGRQ). The Baseline Dyspnea Index (BDI) was used to grade breathlessness. Results: NRDI correlated significantly with VC%predicted (r = -0.36, p = 0.018) and the CPI (r = 0.40, p = 0.01) No significant correlations were found between EMGpara or NRDI and breathlessness, QoL or functional status. Conclusion: EMGpara is a feasible measure in ILD. EMGpara correlates with prognostic markers suggesting potential value as a biomarker integrating important pathophysiological changes in lung mechanics in fibrotic ILDs. The lack of association with QoL measures and BDI requires further investigation.